EFEKTIFITAS MIKROORGANISME LOKAL (MOL) TAPE SEBAGAI AKTIVATOR PEMBUATAN KOMPOS - Panjaitan, Heri (JURNAL MEDIA KESEHATAN, 2014)
Target conducted by this research is to know Efectivity of Local Microorganism activator (MOL) Tape to time depth forming of organic garbage compost. This research type represented experiment using desain "control with posttest". This research used control group and treatment. Research Analysis used analysis of univariat presented in the form of tables of frequency distribution and bivariate analysis by test One Way Anova continued with test of LSD. Result of research known that addition of dose of MOL 25 ml represent most effective form compost with time depth 11,6 day with = 0,000 = 0,05 that there is difference having a meaning of among/between time depth forming of compost to addition of MOL activator.